G288(P) Paediatric sepsis mortality in a single centre over a 7 year period – diagnoses and management. (24th May 2017) - McCarthy, KN; Nicholson, AJ
Abstract : Introduction: It is recognised that early recognition and treatment of sepsis improves outcomes and reduces mortality. The aim of this study is to review patient characteristics, diagnosis, and management in cases of sepsis mortality in a tertiary paediatric hospital over a 7 year period. Methods: We undertook a retrospective review of registered deaths in children in Ireland from 2006–2012. Of 2744 registered deaths, 523 were recorded as due to sepsis. Of these, 434 were excluded as they were cases of neonatal sepsis or occurred in patients with underlying conditions. The remaining 89 cases occurred in children who were previously healthy, 22 of which were registered in TSCUH. Results: The medical records for 17 or the 22 patients were available. The age range was from 1–143 months with a mean of 32.2 months. The distance from primary residence to the tertiary hospital ranged from 2.5 to 218 km with a mean of 55.7 km. 8 (47%) were admitted via ED and 9 (53%) were transferred to ICU from another hospital. The duration of admission ranged from 0 – 250 hour with a mean of 20.5 hour. 76% (n=13) had a duration of admission less than 24 hours. The most common diagnoses following death/post mortem were invasive pneumococcal disease (35%, n=6), meningococcal septicaemia (29%, n=5) and bronchopneumonia (12%, n=2). An organism was identified on culture/PCR in 82% (n=14). The organisms identified included Streptococcus Pneumoniae (35%), Neisseria Meningitidis B (29%), Salmonella/Rotavirus (6%), E. Coli (6%), and Adenovirus (6%). All elements of the paediatric sepsis 6 care bundle were recorded to have been delivered in 29% of patients (n=5). Within the first hour oxygen was administered in 66% (n=11), IV access obtained in 100%, IV broad spectrum antibiotics in 46% (n=7), IV fluid resuscitation in 86% (n=13) and the involvement of a senior clinician documented in 60% (n=9). Conclusions Sepsis mortality remains an important concern in paediatrics although the number of deaths in previously healthy children is low. In total, 53% of patients that died underwent transfer during their care highlighting the importance of paediatric transfer/retrieval services. In this series the full sepsis 6 protocol was completed in only 29% of cases with just 46% receiving IV antibiotics<1 hour highlighting the importance of prompt recognition and management of suspected sepsis.